Carbon footprint of industry-sponsored late-stage clinical trials - Michael Collins; Neil Mackillop; Jayesh Shah; Thomas Costelloe; Daniel Öhman (BMJ Open)
Objectives To quantify the carbon footprint from a sample of pharma industry sponsored phase III trials. To develop an approach that can readily be applied to future trials by AstraZeneca and other trial sponsors.Design Life cycle assessment including all the sources of carbon emissions associated with a completed, an ongoing and a planned clinical trial. The methodology followed the guidance on appraising the sustainability of Care Pathways, developed by the UK National Health Service in collaboration with parties across the healthcare system.Setting Three multicentre late phase trials. One completed heart failure trial, one ongoing oncology trial and one asthma trial with the addition of devices to be representative of current practice.Participants The three trials had a total number of 7412 participants.Main outcome measures Total carbon emissions from each trial, the drivers of those emissions and the emissions per patient.Results The total carbon footprint for the cardiovascular trial was calculated as 2498 tonnes carbon dioxide equivalents (CO2e), the first 3 years of the oncology trial resulted in 1632 tonnes CO2e and the respiratory trial 1437 tonnes CO2e.Conclusions We have shown that it is feasible to perform a retrospective life cycle assessment to appraise the carbon footprint of large clinical trials and confirmed that phase III trials result in significant emissions. Having identified all the drivers of emissions and their magnitude, we are well placed to develop a plan for achieving net-zero carbon clinical trials. Now it is possible to expand the use of life cycle assessment to planned studies so that scientific aims can be achieved with a minimum of carbon emissions. We encourage other trialists to apply the same methodology as a necessary first step in reducing the carbon footprint of clinical trials.